2020
DOI: 10.1155/2020/1871984
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of CILP2 Are Elevated in Coronary Heart Disease and Associated with Atherosclerosis

Abstract: Background and Objectives. Genome-wide association studies (GWAS) have shown that cartilage intermediate layer protein 2 (CILP2) is associated with blood lipid levels and coronary heart disease (CHD). However, no study has reported whether CILP2 is related to atherosclerosis in humans. The purpose of the current study is to identify the associations between CILP2 and atherosclerosis in vitro and in vivo. Methods and Results. Circulating CILP2 levels (measured by ELISA) were compared to various insulin resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Article ll OPEN ACCESS CILP2 is a secreted protein that is associated with high-density lipoprotein cholesterol (HDL-C), but its function in embryonic brain development is unknown (Hu et al, 2020). Our research showed that CILP2 could interact with Wnt3a, which is a ligand that activates the canonical Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Article ll OPEN ACCESS CILP2 is a secreted protein that is associated with high-density lipoprotein cholesterol (HDL-C), but its function in embryonic brain development is unknown (Hu et al, 2020). Our research showed that CILP2 could interact with Wnt3a, which is a ligand that activates the canonical Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 83%
“…We noticed that the expression of CILP2, a secreted protein, was downregulated to the greatest extent, which was consistent with the results of qPCR (Figure 6F). Previous studies have found that CILP2 exists in the circulating blood and plays a vital role in the normal func-tion of blood vessels (Hu et al, 2020;Wu et al, 2019), but its potential function in brain development has not yet been reported. We found that CILP2 was widely expressed in ECs, which was similar to RNF20 (Figure S6A).…”
Section: Cilp2 As the Downstream Target Of Endothelial Rnf20 Mediates...mentioning
confidence: 98%
“…CILP2 is a secreted glycoprotein [ 16 ]. CILP2 was confirmed to be associated with atherosclerosis, according to Hu et al (2020), who revealed that CILP2 regulates the transcription of CD36 through the peroxisome proliferator-activated receptor gamma (PPARγ) pathway, thereby increasing the uptake of lipids by cells and resulting in atherosclerosis [ 17 ]. Luo et al (2017) reported that the rs16996148 genetic locus in CILP2 strongly influenced the risk of dyslipidemia in the Chinese population [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these five DE genes had opposite regulation directions in F and M HUVECs: all were down-regulated in F but up-regulated in M HUVECs from PE. These DE genes include Activity Regulated Cytoskeleton Associated Protein (ARC) and Cartilage Intermediate Layer Protein 2 (CLIP2), both of which are important for intercellular microRNA transportation via extracellular exosome(Pastuzyn et al ., 2018; Hu et al ., 2020). Thus, fetal sex-specific dysregulation of these intercellular microRNA transportation-related genes may contribute to PE-dysregulated miR-29a/c-3p in HUVECs and fetoplacental tissues.…”
Section: Discussionmentioning
confidence: 99%